2012
DOI: 10.3109/08916934.2012.710860
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate modulates antioxidant and DNA repair-related proteins in exocrine glands of a primary Sjogren's syndrome mouse model prior to disease onset

Abstract: The autoimmune disorder primary Sjogren's syndrome (SS) is associated with xerostomia and xerophthalmia. SS pathogenesis involves both genetic/epigenetic and environmental factors. A major potential contributor is oxidative stress associated with damage to cellular components, including DNA. We reported previously that the green tea polyphenol epigallocatechin-3-gallate (EGCG) normalizes the elevated levels of proliferating cell nuclear antigen (PCNA), a key component of DNA repair, in the NOD mouse model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The majority of this reduction was not due to cytotoxicity, indicating a more complex dose response pattern than simple induction. A down-regulation of PRDX6 was not observed in EGCG-fed animals, consistent with serum levels not reaching inhibitory/non-inducing concentrations (13). …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The majority of this reduction was not due to cytotoxicity, indicating a more complex dose response pattern than simple induction. A down-regulation of PRDX6 was not observed in EGCG-fed animals, consistent with serum levels not reaching inhibitory/non-inducing concentrations (13). …”
Section: Discussionmentioning
confidence: 52%
“…Previously, we showed that levels of PRDX6 were reduced before those of the other two enzymes (13). This suggests that PRDX6 plays a key role in maintaining the antioxidant capacity in exocrine glands, consistent with a known role in providing defensive activity against oxidative stress (24).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Consequently, these actions facilitate protective efficacy against ROS-induced apoptosis and tissues destruction [23][24][25][26][27][28]. Additionally, EGCG administration to animal models of autoimmune diseases has been reported to mitigate symptoms and improve the pathological features of autoimmune lesions in rheumatoid arthritis [29,30], multiple sclerosis (experimental autoimmune encephalomyelitis in the animal model) [31], type I diabetes [32], lupus nephritis [33], and Sjögren's syndrome [34][35][36]. EGCG administration has been demonstrated to reduce the autoimmune-induced lymphocytic infiltration in the sialadenitis of NOD mice, a murine model of Sjögren's syndrome [36], but the mechanisms of its suppressive and protective actions on ROS-induced tissue injury of salivary glands in this lesion are completely unexplored.…”
Section: Introductionsmentioning
confidence: 99%